Persepsi Mahasiswa Terhadap Mata Kuliah Sistem Informasi : Studi Kasus Mahasiswa Jurusan Akuntansi Universitas Andalas - Juita, Verni (Jurusan Akuntansi Politeknik Negeri Padang, 2013)
The growing needs for accountants, especially for those who can use and understand information technology, has encouraged accounting programs at the higher education level to offer information system courses. Given this fact, this study aims to (1) assess the students’ perception on the importance and relevance of the information system courses for their major and future works, (2) examine the relationship between the student’s awareness on information system subjects and their performance in these subjects, (3) identify the factors influencing the students’ perception on teaching practices in information system courses. The data was collected through questionnaires which were distributed to accounting students in the Faculty of Economics, Andalas University. This research found that a better understanding on teaching materials of the information system courses have helped students to understand other subjects taught in the accountancy program. Moreover, the student’s motivation, views and the lecturer’s teaching methods and knowledge are the main contributors for the student’s success in these courses.